Environmentally-Induced (Extrinsic) Skin Aging: Exposomal Factors and Underlying Mechanisms - Krutmann, Jean; Schikowski, Tamara; Morita, Akimichi; Berneburg, Mark (Journal of investigative dermatology, 2021)
As a barrier organ, the skin is an ideal model to study environmentally-induced (extrinsic) aging. In this review, we explain the development of extrinsic skin aging as a consequence of skin exposure to specific exposomal factors, their interaction with each other, and the modification of their effects on the skin by genetic factors. We also review the evidence that exposure to these exposomal factors causes extrinsic skin aging by mechanisms that critically involve the accumulation of macromolecular damage and the subsequent development of functionally altered and/or senescent fibroblasts in the dermal compartment of the skin.